Interação de cidadãos com plataformas de grafos de conhecimento: um estudo crítico sobre perfis, funcionalidades e recursos interativos sob a luz da interação humano-dados - Belizario, Mateus Guimarães (2023)
Enabling citizens to use the data generated by urban environments is essential for the development of smart cities, and the use of Knowledge Graphs (KG) opens new possibilities in several domains. The problem is that building and interacting with Knowledge Graphs has been restricted to the technical community, which may limit wide adoption of this type of technology. There are user profiles in smart cities such as administrators, urban planners, and researchers that could make optimal use of the data, but unfortunately cannot use this type of data because they depend on technical training to interact with these knowledge bases. A key solution to overcome this obstacle is to allow the interaction of the data in a coherent and readable way, allowing the web semantic non-specialist and non-technical audience to get a good understanding of its structure. In this context, studies in the field of Human-Data Interaction (HDI) provide possible avenues on how to improve the interaction of different users with data. Thus, the goal of the research is to understand how interaction platforms with knowledge graphs can be developed to allow people without technical knowledge in web semantics and graphs to interact and take advantage of this data in smart cities. To achieve this goal, the profiles of the citizens present in the context of smart cities were identified, as well as their particularities and needs regarding the use of data, the functionalities in which they are interested in such platforms and the interaction resources that can facilitate the contact of non-technical people with these databases. With the inputs collected, a low fidelity prototype was developed and used in communicability evaluations with people to understand the consequences of using adequate interaction resources.